WASATHIYAH: THEORY AND PRACTICE IN MUHAMMADIYAH FATWA DURING THE COVID-19 PANDEMIC الوسطية بين النظرية والتطبيق في الفتاوى المحمدية خلال جائحة كوفيد 19 : دراسة تحليلية - Fajar Rachmadhani (Universitas Muhammadiyah Surakarta, 2022)
This study aims to analyze the moderate attitude (washathiyyah) that characterizes religious understanding in the Muhammadiyah Movement, especially in the conditions of the covid-19 pandemic, which until now has not ended. Muhammadiyah through its fatwa institutions, the Majelis Tarjih dan Tajdid have issued circulars or guidelines for the implementation of worship during the covid-19 pandemic, as a form of response to the problems that arise in the midst of a very diverse society in responding to the conditions of this covid pandemic, there are some people who are indifferent even underestimate the issue of this pandemic, by not complying with the health protocols that have been made by the government there are also some others who are too excessive in responding to it, resulting in looting or hoarding of goods, even panic buying that occurs in several places. So, this is where the role of Muhammadiyah as a moderate Islamic movement is to contribute both morally and materially, one of which is by providing moderate religious understanding in responding to this pandemic. This research includes qualitative research that focuses on library research which is descriptive analytical based on text studies, In this case, the researchers made Muhammadiyah Central Leadership Circular Number 02/EDR/1.0/E/2020, regarding Worship Guidelines. In the Covid-19 Emergency and several other Tarjih fatwas related to guidelines for the implementation of worship during the Covid-19 pandemic as primary data. To analyze the data, the researcher used qualitative analysis using the method of content analysis. This method is used to draw conclusions through efforts to bring out the characteristics of the message which is carried out objectively and systematically. الملخص : تهدف هذه الدراسة إلى تحليل الموقف الوسطي الذي أصبح سمة من سمات الجمعية المحمدية وخصائصها، وخاصة في حالة انتشار جائحة كوفيد-19. لقد أصدرت الجمعية المحمدية من خلال مجلس الترجيح والتجديد التابع لها الفتاوى والإرشادات في أداء العبادات أثناء جائحة كوفيد-19، استجابة للمشاكل التي يواجهها المجتمع الإندونيسي في شتى مواقفهم تجاه هذه الجائحة، منهم الأشخاص الذين لا يبالون بل يقللون من شأن قضية هذه الجائحة، من خلال عدم الامتثال للنظم الصحية التي وضعتها الحكومة، وبعض الآخر يبالغون في الاستجابة لها، مما يؤدي إلى نهب البضائع أو احتكارها، والشراء الذعر الذي حدث في العديد من الأماكن. فمن هنا، كان للجمعية المحمدية -بصفتها حركة إسلامية وسطية- دور هام في المساهمة معنويًا كان أو وماديًا، من خلال توفير المفاهيم الدينية الوسطية للمجتمع في الاستجابة لهذه الجائحة. يعتبر هذا البحث بحثا نوعيا بحيث يركز على البحث في المكتبات وهو بحث تحليلي وصفي يعتمد على دراسات نصية، وفي هذه الدراسة قام الباحث بدراسة منشور القيادة المركزية المحمدية رقم 02 / EDR / 1.0 / E / 2020 بشأن إرشادات العبادات خلال جائجة كوفيد-19 كبيانات أولية. ولتحليل البيانات استخدم الباحث المنهج التحليل النوعي بحيث تستخدم هذه الطريقة لاستخلاص النتائج من خلال الجهود المبذولة لإخراج خصائص الرسالة التي يتم تنفيذها بشكل موضوعي ومنهجي.